Implementasi Manajemen Pemasaran Pendidikan Dalam Perspektif Islam Di MA Al-Ahliyah Cikampek Karawang - Zayyin Saifuddin; Sya'roni Ma'shum; Hinggil Permana (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2021)
This article discusses educational marketing to overcome competition with other institutions. Marketing makes a big difference to the number of students, with the application of good educational marketing management and does not conflict with Islam, the institution will win the competition and will increase public interest. The method used in this study is a qualitative technique with data collection techniques through observation, interviews, documentation, and literature. The data analysis technique used is synthetic analysis with the stages of data reduction, data display (displaying data), drawing conclusions and verification. The results of the study that in the implementation of education management in an Islamic perspective at MA Al-Ahliyah Cikampek Karawang are; 1) planning, which consists of market identification, market segmentation, targeting, placement, and product differentiation 2) organizing 3) directing 4) supervision.